COMPARISON OF ENERGY EFFICIENT AODV AND AODV PROTOCOL USING NS - Vaibhav N Palav, Vijaykumar Kawde,Shraddha Kunkunkar,Preeti Motwani (International Journal of Research Science and Management, 2017)
MANETs consists of many mobile nodes that nodes perform operation like selection of nodes for paths from source to destination. Normally traditional protocols are used for this type of operations. In such traditional protocols packets are routed using store and forward approach. These packets are routed though each intermediate nodes in path from source to destination. Hence routing packets is very costly process. This paper work proposes EE-AODV protocol that uses algorithm which is energy efficient. To run this algorithm NS 2.35 Software is used. This algorithm uses two phase: energy survival phase and energy saving phase. Also it focuses on the shortest path feature and reliability of the network while establishing the connection through intermediate nodes.